'Bad' Jobs in a 'Good' Sector: Examining the Employment Outcomes of Temporary Work in the Canadian Public Sector. (August 2019) - Stecy-Hildebrandt, Natasha; Fuller, Sylvia; Burns, Alisyn
Canada's public sector has historically provided good jobs, but its increasing reliance on temporary workers has important implications for job quality. We compare temporary and permanent workers in the public sector on three dimensions of job quality (employment security, access to benefits and income trajectories) to assess whether favourable conditions in the public sector are extended to temporary employees, or whether polarization between temporary and permanent workers is the norm. We find provisions related to employment security and access to leave benefits in public sector collective bargains are clearly two-tiered. Drawing on nationally representative panel data, we also find a persistent earnings gap between matched permanent and temporary employees. Further, although temporary public sector workers out-earn their private sector counterparts, the earnings disadvantage relative to matched permanent workers is more pronounced and longer lasting in the public sector. Underlying this difference is greater persistence in temporary employment within the public sector.